A case study research on Carrefour's foreign investments in South Korea and Japan - Wang, Yue (2013)
The aim of this paper is to apply various concepts of institutional theory in the study of multinational corporations. In particular, a case study approach is adopted to exam the failures of Carrefour, a French multinational retailer in South Korea and Japan. Being one of the largest hypermarket chains in the world, Carrefour has been very successful in its home country. References from various sources are drawn to investigate the reasons of Carrefour’s exits in the two particular countries using institutional theory. As one of the frameworks of institutional theory, “conceptualization of the national environment in terms of regulatory, normative and cognitive pillars” [Vargas-Hernández, 2009] is used in the analysis. It explains how Carrefour failed to attain isomorphism as a result of not conforming to the Pillars framework. Based on the findings, several managerial implications are proposed in order to achieve success in future investments.